(untitled) (Philologia, 2021)
Based on a corpus analysis of words recently produced and established in the English language, within a variety of registers and styles, the paper seeks to outline a number of tendencies having an effect on the process of the establishment of new words in the common lexicon of the language. Whether a word is to be accepted in a language community is not governed by rules of the language. However, it is clear that not all of the outputs of word- formation processes are widely known or used within the community; so, every produced word belongs to the fund of realized items, but few enter the common vocabulary. Nonce formations, on the one hand, are words created for a single speech act or written text, and they rarely become established in the English language, primarily due to the ambiguity, or more precisely, elusiveness, of their meaning which is highly dependant on a particular text or context. On the other hand, scientiﬁc terms and brand names are readily standardized and used, in most cases within specialized registers, their primary characteristics being exactness and transparency.